Anne of Avenue A : a novel - Bellezza, Audrey; Harding, Emily (Gallery Books, an imprint of Simon & Schuster, LLC, 2025)
Anne Elliot broke Freddie Wentworth's heart when she dumped him eight years ago. He was going to study in Buenos Aires and wanted her to come along. She couldn't leave her plans for an MBA behind. Now nothing has gone according to Anne's plans, and it only gets worse when Freddie moves back to New York and into her building in the East Village. It's been years since they've seen each other, and the only thing they have in common is the desire to keep their past in the past. But as their lives become intertwined and feelings resurface, they face a choice: put their hearts on the line or walk away all over again.